Devi Lianovanda Prabandani ANALISIS SPECIAL EVENT ANGKLUNG PRIDE #9 OLEH SAUNG ANGKLUNG UDJO - Devi Lianovanda Prabandani; Rah Utami Nugrahani (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2020)
Angklung Pride is an annual event held by Saung Angklung Udjo to commemorate the ratification angklung asintangible cultural heritage of humanity from Indonesia. This event is done to preserve four pillar of UNESCOwhich was given by them. This four pillar were reserved, promoted, protected, and perpetuated. The objectiveof this research is to obtain deep understanding of the event management process of Angklung Pride #9 bySaung Angklung Udjo using Joe Goldblatt’s Special Event Theory in five stages. Those stages are research,design, planning, coordination, and evaluation. The data was acquired by deep interviews, observations, anddocumentations process. The conclusion of this research divided the event management process in fivestages, which are summarized into three part. Those part are planning, execution, and evaluation. Planningprocess included concept, idea, and theme decision process, organization structure making and job descriptiondistribution, risk management planning, and place and time determining. Execution process aim forconcept, place, event contents, entertainment, and promotion activity implementation. The last is evaluationprocess which included things that can be used for the next Angklung Pride event improvement.